Model Rantai Pasok Pada PT Abhimata Citra Abadi - Dinda Tiara Sani; Fahmi, Muhammad Ainul (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
This research aims to demonstrate and analyze the supply chain model for information technology in telecommunications services used by PT Abhimata Citra Abadi, Jakarta, Indonesia, using qualitative methods. Data was collected through field research and literature study. The field study was carried out through observation and the sampling technique used was purposive random sampling. The results of this research look at the parties involved in the supply chain at a telecommunications service company, namely PT Abhimata Citra Abadi. The research results show that PT Abhimata Citra Abadi has three supply chain models, namely Supplier – Distributor – Consumer, Supplier – Manufacture – Distributor – Consumer, and Supplier – Manufacture – Distributor – Retail – Consumer. In the supply chain model at PT Abhimata Citra Abadi, goods will always go in and out to distributors.